Insecticidal activity of essential oils on Spodoptera frugiperda and selectivity to Euborellia annulipes - Alves,A. C. L. (2024)
Abstract Fall armyworm (Spodoptera frugiperda) is the main species that causes damage to the maize crop in Brazil. In the perspective of studying alternatives of control of this pest that preserve the natural enemies, the aim of this research was to evaluate the insecticidal efficiency of the essential oils of Vanillosmopsis arborea and Lippia microphylla on S. frugiperda and verify the selectivity to the predator Euborellia annulipes. The bioassays were carried out in the Agricultural Entomology Laboratory of the Federal University of Paraiba, using insects, from 3rd instar of S. frugiperda and E. annulipes, originating from mass rearing in the laboratory itself. Dilutions of the oils were performed in Tween® 80 at concentrations of 0, 100, 150 and 200 mg mL-1. 1.0 μL from each dilution was applied to the prothoracic region of the insects. The S. frugiperda mortality was verified by topical contact of V. arborea oil with LC10 = 74.3 mg mL-1 and LC50 = 172.86 mg mL-1, for L. microphyla, LC10 = 51.26 mg mL-1 and LC50 = 104.52 mg mL-1. The observed lethal concentrations for E. annulipes were V. arborea LC10 = 71.3 mg mL-1 and LC50 = 160.2 mg mL-1. While L. microphyla, were LC10 = 50.3 mg mL-1 and LC50 = 134.67 mg mL-1. The essential oils of V. arborea and L. microphylla are efficient in the control of S. frugiperda, but are not selective to the predator E. Annulipes.